Strategi Pengembangan Agrowisata Hutan Mangrove Dewi Bahari di Tangkolak Kabupaten Karawang - Zeni Ayu Lestari; Abubakar Abubakar; Luthfi Nur’azkiya (Peneliti.net, 2022)
Dewi Bahari Mangrove Forest Agrotourism is a tourism that has the potential to develop. However, there are still internal and external constraints, so a strategy is needed to develop it. The purpose of this study is to analyze the strategic position and determine the appropriate alternative strategy in the development of Dewi Bahari Mangrove Forest Agrotourism. The sampling method used is purposive sampling. In this study, the types of primary data and secondary data were used. Primary data was obtained through interviews with a questionnaire tool addressed to eleven respondents. Primary data was also obtained through field observations. While secondary data is obtained from literature studies and information issued by agencies or institutions related to research. Data analysis was carried out qualitatively and quantitatively. Processing data using SWOT analysis that’s with IFAS matrix, EFAS matrix, grand strategy matrix, and SWOT matrix. The results of the study based on the SWOT analysis showed that Dewi Bahari Mangrove Forest Agrotourism was in quadrant I with the suggested alternative strategy was to support an aggressive growth policy (growth oriented strategy). Based on the results of the SWOT analysis, there were also 10 (ten) strategies which included 2 (two) S-O strategies, 3 (three) W-O strategies, 3 (three) S-T strategies and 2 (two) S-W strategies. The appropriate alternative strategies for the development of Dewi Bahari Mangrove Forest Agrotourism are 2 (two) S-O strategies, including : (1) creating events on weekends which are then published on social media as promotions; (2) empower and train community to be able to have businesses related to tourism.